Engagement with perinatal mental health services: a cross-sectional questionnaire survey - Alice Ayres; Renee Chen; Tracey Mackle; Emma Ballard; Sue Patterson; George Bruxner; Alka Kothari (BMC, 2019)
Abstract Background Perinatal depression and/or anxiety disorders are undertreated pregnancy complications. This is partly due to low rates of engagement by women. This study aimed to identify barriers and facilitators to women accessing perinatal mental health services in an outer metropolitan hospital in Queensland, Australia. Methods Data was collected from pregnant women through a cross-sectional survey. Women rated the extent certain factors influenced their engagement. Respondents were separated into three groups: women who were not offered a referral to perinatal mental health services, women who were offered a referral but did not engage, and women who engaged. Results A total of 218 women participated. A response rate of 71% was achieved. 38.1% of participants did not believe themselves knowledgeable about mental illness in the perinatal period, and 14.7% did not recall being asked about their mental health during their pregnancy. Of those participants who recalled being asked about their mental health, 37.1% were offered a referral. Of these, just over a third (36.2%) accepted, and out of this group, 40% attended an appointment. Regardless of referral and engagement status, the factors identified as influencing participant engagement were time restraints, lack of childcare support, and encouragement by family and health care professionals. Stigma was not identified as a barrier. Conclusions Perinatal mental health service engagement could be improved by health services: ensuring universal screening and actively engaging women in the process: assisting with childcare; improving appointment immediacy and accessibility; and educating health care professionals about their influence on women's engagement.